2002
DOI: 10.1053/eujp.2001.0316
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain: evidence matters

Abstract: "He slept less and less; they gave him opium and began to inject morphine. But this did not relieve him. The dull pain he experienced in the half asleep condition at first only relieved him as a change, but then it became as bad, or even more agonizing, than the open pain."--Tolstoy, The Death of Ivan Ilyitch. It comes as a surprise to many pharmacologists that not all pains are relieved by opioids. Those who work in chronic pain are unfortunately only too aware of the problems that such pains can cause. One o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…Although opioids are considered to be less effective for relief of neuropathic pain than for nociceptive pain, 48,49 the frequent use of opioids and the perceived usefulness of this drug reported by some participants deserve further investigation. For example, several investigators 24,50 have suggested that specific neurological subgroups of neuropathic pains may respond to opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Although opioids are considered to be less effective for relief of neuropathic pain than for nociceptive pain, 48,49 the frequent use of opioids and the perceived usefulness of this drug reported by some participants deserve further investigation. For example, several investigators 24,50 have suggested that specific neurological subgroups of neuropathic pains may respond to opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressants have been used for more than 30 years in the clinical management of neuropathic pain (McQuay, 2002) and have been shown to provide analgesia for a variety of neuropathic pain syndromes regardless of the presence of depression (Richeimer et al, 1997;Mico et al, 2006). Many studies have demonstrated the efficacy of antidepressants for the management of diabetic neuropathy (Kvinesdal et al, 1984;Sindrup et al, 1989;Max et al, 1992), postherpetic neuralgia (Watson et al, 1982), poststroke pain (Leijon and Boivie, 1989), post-thoracotomy pain (Keller et al, 1994), and almost all types of neuropathic pain (Saarto and Wiffen, 2005;Sindrup et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…DPN is mainly a progressive distal axonopathy, with loss of feeling and numbness in feet, hands and legs, which may be accompanied by painful tingling or burning sensations [7]. Diabetic neuropathies are painful in more than 15% of patients, a substantial proportion of whom complain of chronic pain [6] and poor response to conventional analgesics [8].…”
Section: Introductionmentioning
confidence: 99%